The Effect of Tiktok Education Videos as A Learning Media for Students English Writing Skills at SMP Swasta Kartika I - 4 Pematangsiantar (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
The purpose of this research is to find out the utilizing of the TikTok application as a media for learning English writing at eighth grade of SMP Swasta Kartika I-4 Pematangsiantar. This research used quantitative with quasi-experimental method approach. Population of this research was eighth grade with 2 classes which consists of 64 students and the sample of this research was 32 students in one class. The technique of collecting data was pre-test and post-test. The technique of analyzing26. data by using SPSS version 27.0. The result of research was Tcount (5.871) > Ttable (1.670) at the significance level α = 0.05 with the degrees of freedom (df) = (32-1=31) for each class so the degrees of freedom is 62. It means that H0 is rejected and Ha is accepted. Based on the evidence from the research results, the post-test has a higher score than the pre-test. From these results it was concluded that there was a significant difference in improving students' writing skills before and after being given treatment using TikTok media as a learning media. Therefore, the researcher believes that using TikTok Application utilized to be used on the students' writing skills in eighth grade of SMP Swasta Kartika I-4 Pematangsiantar. Because the use of TikTok Application as a media for learning English writing skills is highly effective. The students believe that it was a popular new media among Indonesian people. TikTok offers a variety of features, including short educational videos, creative visual storytelling, and an engaging platform which makes it easier for students to learn and practice English writing skills. Certain creative TikTok users have even created special videos to guide English writing practices. The students can be free to express their ideas to improve their writing skills. As a result, the researchers have observed that students who experience using TikTok educational videos have found it beneficial for improving their language writing skills